THE INFLUENCE OF PRODUCT INNOVATION, PRICE, AND BRAND AMBASSADOR ON PURCHASE DECISIONS OF SCARLETT WHITENING IN SANGASANGA DISTRICT - Isti Nur Aziza; Annisa Wahyuni Arsyad; Wira Bharata; Fareis Althalets (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
This study aims to analyze the influence of product innovation, price, and brand ambassador on the purchase decision of Scarlett Whitening in Sangasanga District. Using a quantitative approach with a descriptive method and purposive sampling technique, data were collected from 100 respondents who are active users of Scarlett Whitening products. The results of multiple linear regression analysis indicate that the three independent variables product innovation, price, and brand ambassador have a significant simultaneous effect on purchase decisions with brand ambassador being the most dominant variable. The coefficient of determination, which stands at 50.5%, reflects a fairly strong predictive power of the model. These findings confirm that purchase decisions in the beauty industry are influenced not only by functional aspects such as product quality and pricing, but also by emotional and symbolic factors associated with brand ambassadors. Theoretically, this research reinforces concepts within marketing mix theory and consumer behavior, particularly the role of symbolic communication in shaping buying intentions. Practically, local cosmetic companies are advised to develop continuous product innovations, apply competitive yet value-aligned pricing strategies, and select brand ambassadors with high credibility and strong social resonance among their target market, especially young consumers influenced by popular cultural trends such as the Korean Wave.